2018
DOI: 10.3847/1538-3881/aaee69
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Proto-planetary Nebulae. V. Velocity and Light Curve Analysis of IRAS 17436+5003, 18095+2704, and 19475+3119

Abstract: We have obtained contemporaneous light, color, and radial velocity data for three proto-planetary nebulae (PPNe) over the years 2007 to 2015. The light and velocity curves of each show similar periods of pulsation, with photometric periods of 42 and 50 days for IRAS 17436+5003, 102 days for IRAS 18095+2704, and 35 days for IRAS 19475+3119. The light and velocity curves are complex with multiple periods and small, variable amplitudes. Nevertheless, at least over limited time intervals, we were able to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…In this paper, we report on the search for periodic brightness variations in the light curves of five medium-bright PPN candidates which appear to have O-rich or mixed chemistries. This follows our earlier variability studies of four bright (V = 7-11 mag) O-rich PPNe (Hrivnak et al 2015b(Hrivnak et al , 2018. Most of our previous variability studies have been of C-rich PPNe in the Milky Way Galaxy (Hrivnak et al 2010(Hrivnak et al , 2013(Hrivnak et al , 2020 and in the Magellanic Clouds (Hrivnak et al 2015a).…”
Section: Introductionsupporting
confidence: 87%
“…In this paper, we report on the search for periodic brightness variations in the light curves of five medium-bright PPN candidates which appear to have O-rich or mixed chemistries. This follows our earlier variability studies of four bright (V = 7-11 mag) O-rich PPNe (Hrivnak et al 2015b(Hrivnak et al , 2018. Most of our previous variability studies have been of C-rich PPNe in the Milky Way Galaxy (Hrivnak et al 2010(Hrivnak et al , 2013(Hrivnak et al , 2020 and in the Magellanic Clouds (Hrivnak et al 2015a).…”
Section: Introductionsupporting
confidence: 87%
“…The RV amplitudes are small (<4.0 km/s, Hrivnak et al [12]) and the periods found in the RV data are in the range 35 to 103 days, similar to the pulsation periods of the objects. So far, no clear evidence for long-period RV variations due to binary companions has been found in any of these objects.…”
Section: Radial Velocity and Photometrysupporting
confidence: 63%
“…However, over limited time intervals during 2007-2015, we were able to identify dominant periods in the light, color, and velocity curves and compare the phasing of each. See figures in Hrivnak et al [12] which shows the phased light, color, and velocity curves of the objects. The color curves appear to peak with or slightly after the light curves while the RV curves peak about a quarter of a cycle before the light curves.…”
Section: Radial Velocity and Photometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of pulsation in PPNe have also been published by Arkhipova and collaborators (e.g., Arkhipova et al 2010Arkhipova et al , 2011. For the brighter ones (V ≤ 10.5 mag), we have also compared their radial velocity curves with their light curves to determine the phase relationship between their brightness, temperature, and size (Hrivnak et al 2013(Hrivnak et al , 2018). Here we present our observed light curves for five medium-bright objects.…”
Section: Introductionmentioning
confidence: 99%